Evolution and attribution of the water yield coefficient in the Yiluo river basin - Hou, Jun; Yan, Denghua; Qin, Tianling; Liu, Shanshan; Yan, Sheng; Li, Jian; Abebe, Sintayehu A.; Cao, Xuchao (Frontiers in Environmental Science, 2022)
Abstract: This article aims to detect the evolution and attribution of historical and future water yield coefficient. Based on the calibrated and validated water yield coefficient model in the Yiluo River Basin, the coefficient in 2000-2020 were simulated, as well as in 2030-2050 under four Shared Socioeconomic Pathways (including SSP126, SSP245, SSP370 and SSP585). Then the spatio-temporal evolution of historical and future water yield coefficient were analyzed. Moreover, the geographical detector model was used to detect the impacts of climate, land use and terrain factors on water yield coefficient. The results showed the water yield coefficient fluctuant increased by 8.53% during 2000-2020, of which the coefficient of the farmland increased by 10.47% and the forestland decreased by 8.93%. The coefficient was the highest under the SSP370 scenario and the lowest under the SSP585 scenario in 2030-2050. Compared with 2000-2020, the coefficient of the two scenarios increased by 12.2% and 2.0%, of which the coefficient of the farmland increased by 13.2% and 2.7%, and the forestland decreased by 0.9% and 14.6%, respectively. Driving factors detection indicated the land use types had the strongest explanatory power to water yield coefficient, the explanatory value reached 26.5% in 2000-2020, and will exceed 29.5% in 2030-2050. In addition, the interaction between any two factors was stronger than a single factor. The research provides scientific support for precise managing watershed water-land resources.